2017
DOI: 10.4314/ijah.v6i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV Testing Among Sexually Active Young People in Zambia

Abstract: ……………………………………………………………………………… AbstractThis study used data from the 2013 Zambia Demographic Health Survey (ZDHS) based on a nationally representative sample carried out by Central Statistical Office of Zambia. This paper analyzed a special module designed to collect information on the extent of the uptake of HIV testing by sexually active young people in Zambia 131Copyright © International Association of African Researchers and Reviewers, 2006-2017: www.afrrevjo.net/ijah Indexed African Journals Online (AJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…This can sensitise the AGYW on the importance of HIV testing and provide information on where to get HIV tested. This has also been found by other studies from Ethiopia [ 33 ] and Zambia [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This can sensitise the AGYW on the importance of HIV testing and provide information on where to get HIV tested. This has also been found by other studies from Ethiopia [ 33 ] and Zambia [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the poor may be more preoccupied with meeting their daily needs and HIV testing may not be a priority for them. Other studies (see Jooste et al 2020 [ 21 ], Cemin et al 2012 [ 30 ], Treves-Kagan et al 2017 [ 31 ], Matovu et al 2013 [ 32 ], Ibrahim et al [ 24 ], Molla et al [ 33 ], Menon et al [ 34 ]) also found that wealthy individuals are more likely to be tested for HIV as compared to poor individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Zambian study [ 17 ], this study found an association between inconsistent condom use and self-reported HIV testing. After having unprotected sex, the fear and anxiety that one may have of having been infected can influence individuals to test for HIV.…”
Section: Discussionsupporting
confidence: 85%
“…This study found that older age for AGYW (20–24 years) was associated with self-reported HIV testing. The same association was also determined among sexually active AGYW in Zambia [ 17 ]. The association can be attributed to the fact that older AGYW may be more knowledgeable about HIV testing [ 18 ], probably due to their higher level of education as these AGYW are more likely to have finished secondary school education than the 15–19 year olds.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, young women living in rural areas had lower odds of being tested for HIV [15][16][17]. Young women who had multiple sexual partners, those who ever had been pregnant, those who started sexual intercourse after 15 years old, those who had good knowledge about HIV, those who discussed about HIV with mother or female guardian, those who had history of sexually transmitted infections and those who attended antenatal care had higher odds of being tested for HIV [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%